Impact of psychological distress and psychophysical wellbeing on posttraumatic symptoms in parents of preterm infants after NICU discharge - Serena Salomè; Giuseppina Mansi; Carmine V. Lambiase; Marta Barone; Valeria Piro; Marcella Pesce; Giovanni Sarnelli; Francesco Raimondi; Letizia Capasso (BMC, 2022)
Abstract Backgorund Parents after Neonatal Intensive Care Unit (NICU) hospitalization of preterm infant may develop psychopathological symptoms. The aim of the study was to determine how parental stress and psychophysical wellbeing affect posttraumatic symptoms (PTTS) in parents during the first year after NICU discharge. Moreover, this study aimed to explore any gender-specific difference in psychological distress among mothers and fathers. Methods Prospective study design from September 2018 to September 2019. 20 pairs of parents of preterm infants admitted to a tertiary-level NICU were enrolled. Primary outcome was evaluation of PTTS in parents of preterm infants at one year after NICU discharge through Impact of Event Scale- Revised. Secondary outcomes were: impact of parental stress, psychophysical wellbeing, anxiety and depression respectively through Parental Stressor Scale: NICU, Short Form Health Survey-36(SF-36), Self-rating Anxiety Scale and Self-rating Depression Scale. Results Mothers experienced higher rates of PTTS than fathers across the first year after NICU discharge (55% vs 20%). Maternal avoidance symptoms were associated with perception of their own infant look. Emotional aspects linked to maternal role predicted 36,8% of their hyperarousal symptoms. Maternal PTTS severity was predicted by their social functioning. Paternal mental health was associated both with maternal and paternal intrusive symptoms.. Maternal stress was associated with paternal avoidance symptoms. Paternal mental health predicted their hyperarousal symptoms (40%) and PTSD severity (52%). Conclusions Parents who experienced NICU hospitalization of their own infant are at heightened risk to develop psychopathological symptoms. According to our initial hypothesis, investigating parental psychophysical wellbeing, through SF-36, originally provides a valuable support to detect parents at higher risk to develop posttraumatic outcomes across the first year after NICU discharge. In addition, paternal depression deserves to be taken into account since hospitalization as it could impact paternal PTSD development. Finally, these findings provide an initial evidence of gender-related patterns in PTSD development and psychological distress among mothers and fathers across the first year of their infant.